Faktor – faktor yang mempengaruhi minat membayar zakat pada masyarakat Kabupaten Sidoarjo - Ridho Muhamad; Ahmad Ajib Ridlwan (LPMP Imperium, 2023)
The purpose of this study was to identify the effect of religiosity and income levels on the intention to pay zakat in the people city of Sidoarjo. The research method used is quantitative research with multiple linear regression analysis techniques. The sampling technique uses random sampling by distributing questionnaires according to predetermined characteristics. The results of this study state that religiosity and income levels have a positive effect on the intention to pay zakat. These results conclude that people in the city of Sidoarjo make aspects of religiosity and income levels as factors in paying zakat in their intention to pay zakat. Public interest statementIn this study, we seek to provide new insight about factors in the intention to pay zakatArticle HistoryReceived 25 Dec 2022 | Revised: 15 Jan 2023 | Accepted: 17 Jan 2023 | Online First: 25 Jan 2023